Responsive-Anticipative Coalition-building Method in The Policy of Integration Between Diniyah Takmiliyah and Formal Elementary School Education Institutions in East Jawa - Rahman, Moh. Rifqi; Fuad, Ah. Zakki; Zuhri, Achmad Muhibin (Jurnal Tarbiyatuna, 2023)
The lack of communication between the education office and the ministry of religion in the implementation of Diniyah Takmiliyah education which has led to the emergence of new Diniyah Takmiliyah institutions, resulting in overlapping, and the low participation of parents in involving their children in Diniyah Takmiliyah education are some of the problems in the implementation of the Diniyah Takmiliyah integration policy with formal educational institutions. The objective of this research is to analyze and formulate the way of regency government in building the coalition with the executive parties of the policies of Diniyah Takmiliyah integration with formal educational institution in Sumenep and Pasuruan Regency and in building coalitions that lead to communication strategies so that research results can describe solutions to existing problems. This research is qualitative research with an institutional approach and an actor approach. The data collection technique used is document review, observation, and interviews, while the data analysis is done through several stages: data reduction, data presentation, and conclusions. The research results show that the method of building coalitions can be done in two ways. They are anticipatory and responsive. The findings of these two strategies are discussed further in the research. Furthermore, this research recommends effectiveness or factorial analysis to provide validation of the findings of this research.